PENGGUNAAN STORYTELLING UNTUK MEMBANTU SISWA MTS HUSAINIYAH CICALENGKA MENGENAL PROFESI TEKNOLOGI INFORMASI - Suharsono, Teguh Nurhadi; Gunawan; Sukmana, Rini Nuraini; Rahman, Fauzan Andriana; Ammarulloh, Sendhy Maula (Jurnal Abdimas Sang Buana, 2024)
Mts Husainiyah is an educational institution located in Panenjoan Cicalengka, Bandung Regency with a total of 152 female students. In facing this digital era, teenagers who have just reached an early age will be faced with changes field in the rapidly evolving fin the field of information technology that is rapidly evolving. The purpose of this community service project as an initial introduction to professions related to the field of information technology, so it is hoped that it will be useful in this digital era. The method used to provide an introduction to any profession related to the field of information technology is the Storytelling Method, which is a method of telling stories and providing real examples based on the experiences of volunteers who work in the field of information technology. Students will write their goals on a goal tree sheet. Based on the recapitulation results of the dream tree, it turns out that 25.27% of the students chose professions related to the field of information technology as many as 25.27% of the 91 students who were given an introduction. The initial target for students who choose a profession in the field of information technology is 20%, so this exceeds the target and the Storytelling Method is effective for use in this community service activity.